CRIMINAL LIABILITY IN PROTECTED WILDLIFE SMUGGLING:" "JURIDICAL ANALYSIS OF DECISION NUMBER 106/PID.SUS/2024/PN.TJB - Maulida Agusdila Rosa Sitorus Pane (NOMOI Law Review, 2026)
Wildlife protection is a crucial aspect of preserving Indonesia's biodiversity, yet increasingly widespread smuggling practices pose a serious threat to protected species survival. This study analyzes criminal liability in the case of pangolin scale smuggling via KM. Fajar 99, adjudicated in Decision No. 106/Pid.Sus/2024/PN.Tjb. Using normative legal research with case, statutory, and conceptual approaches, findings indicate that the judge prioritized substantive justice, determining that the ship master (Syamsir) lacked criminal intent as he merely performed navigational duties based on official documents. Legal responsibility should instead be directed at the exporter (CV. Pribumi Bersatu) and shipping company (PT. Melda Jaya) as the principal actors, and Customs for failing to conduct mandatory boatzoeking inspections. This study recommends applying corporate criminal liability, strengthening Customs inspection mechanisms, and enhancing inter-agency coordination.